URBANIZATION AND ACELERATION THE EROSION PROCESS IN SANTA MARIA CITY – RS – BRASIL - Bernadete Weber RECKZIEGEL; Luís Eduardo de Souza ROBAINA; Vagner Paz MENGUE (Sociedade & Natureza)
In the stage of development in which contemporary society meets up with theglobalization process dominates the world. One of the consequences of that process is theaggravation of social differences and urbanization manner of peripherical countries, whichhas as characteristics the pronounced spatial concentration and the accelerated rhythm ofincrease, tending to present big agglomerations, many times wanting infra-structural basicservices. The result of that process is social spatial segregation of urban area.According to Coelho (2001), human beings in meeting in a determined physical spaceaccelerate the environmental degradation processes. Following this logic, degradation growsup in proportion to populational concentration increases. So, cities and environmentalproblems create between them a rigid cause-effect relation.In Santa Maria, that process becomes evident in many places of the city, where theestablishment of lots with irregular occupation of environmentally fragile areas have beenoccurring. Herewith, parts at the headwater in the western part of the city were incorporated tothe urban area of the municipal district. One of those areas in the region is known as NovaSanta Marta, where happen problems related to physical environment which has enlargedtogether with the urban occupation of the area, that those ones linked to erosion in the shapeof gully erosion in the headstreams are more significative.In that context, this current work aims to study the influence of the antropic action,especially urbanization, in the unchaining and evolution of the accelerated erosive processesin Nova Santa Marta.